2022
DOI: 10.1093/mnras/stac3421
|View full text |Cite
|
Sign up to set email alerts
|

Velocity-coherent substructure in TMC-1: inflow and fragmentation

Abstract: Filamentary structures have been found nearly ubiquitously in molecular clouds and yet their formation and evolution is still poorly understood. We examine a segment of Taurus Molecular Cloud 1 (TMC-1) that appears as a single, narrow filament in continuum emission from dust. We use the Regularized Optimization for Hyper-Spectral Analysis (ROHSA), a Gaussian decomposition algorithm which enforces spatial coherence when fitting multiple velocity components simultaneously over a data cube. We analyze HC5N (9-8) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
1
1
0
Order By: Relevance
“…The resulting molecular abundances, with respect to an assumed N T, H 2 ( ) = 1 × 10 22 cm −2(Gratier et al 2016), were converted to column densities and compared with the observed values. This N T, H 2 ( ) value is consistent with the H 2 column density map of TMC-1 derived from the dust continuum emission observed by Herschel(Smith et al 2023).…”
supporting
confidence: 88%
“…The resulting molecular abundances, with respect to an assumed N T, H 2 ( ) = 1 × 10 22 cm −2(Gratier et al 2016), were converted to column densities and compared with the observed values. This N T, H 2 ( ) value is consistent with the H 2 column density map of TMC-1 derived from the dust continuum emission observed by Herschel(Smith et al 2023).…”
supporting
confidence: 88%
“…If the inclination to the line of sight is 12°and 35°for Fil1 and Fil2, respectively, the core spacings of Fil1 and Fil2 become 0.64 pc and 0.28 pc, coming close to four times each filament's width. However, the quasiperiodic spacings of fragments in filaments in observations (e.g., Smith et al 2023) and simulations (e.g., Clarke et al 2016) do not always match the expectations of classical cylinder model. Zhang et al (2020) used Herschel far-infrared data and investigated the filaments and cores in the California-X region.…”
Section: Discussionmentioning
confidence: 81%